The Effects of Cognitive Behavioral Therapy for Insomnia on Multidimensional Perfectionism. Issue 2 (March 2023) - Johann, Anna F.; Feige, Bernd; Hertenstein, Elisabeth; Nissen, Christoph; Benz, Fee; Steinmetz, Lisa; Baglioni, Chiara; Riemann, Dieter; Spiegelhalder, Kai; Akram, Umair
Highlights: Perfectionism was related to dysfunctional cognition and sleep-effort at baseline. Patients receiving treatment presented an increase in total perfectionism scores posttreatment. Organizational behavior and parental expectations increased in those receiving treatment. Patients receiving treatment displayed a reduction in doubts about action posttreatment. Abstract: Perfectionism is related to insomnia and objective markers of disturbed sleep. This study examined whether multidimensional perfectionism is related to dysfunctional beliefs about sleep, sleep-effort, pre-sleep arousal, and polysomnography-determined markers of sleep among individuals with insomnia. The effects of cognitive behavioral therapy for insomnia (CBT-I) on perfectionism was also examined. This was a secondary analysis of a randomized controlled trial on CBT-I. Forty-three insomnia patients were randomized to treatment (receiving CBT-I) or waitlist control groups. Sleep was recorded using polysomnography at baseline. Participants completed measures of perfectionism, dysfunctional beliefs about sleep, sleep-effort and pre-sleep arousal at baseline and posttreatment. Total perfectionism scores and doubts about action, concern over mistakes and personal standards were each significantly related to increased sleep effort, pre-sleep arousal and dysfunctional beliefs about sleep at baseline. Patients receiving treatment displayed increased total perfectionism scores posttreatment d  = .49. In those receiving treatment, levels of organization d  = .49 and parental expectations d  = .47 were significantly increased posttreatment, relative to baseline. In line with the literature, our results confirm that perfectionism is related to insomnia. Here, insomnia was related to increased sleep effort, pre-sleep arousal and dysfunctional beliefs about sleep. The propensity to maintain a high standard of order and organization may be elevated following CBT-I, considering the treatment protocol expects patients to strictly adhere to a set of clearly defined rules. Levels of parental expectations may be increased following CBT-I since the patient-therapist-relationship may trigger implicit expectations in patients which are reminiscent of their relationship to their parents.